Common sense based automatic query expansion. Issue 7 (2nd October 2020) - Jain, Goonjan; Bansal, Achal
Abstract: Query expansion techniques are widely applied for improving the efficiency of the textual information retrieval systems. We expand the original query with additional relevant terms which helps in better understanding of the query and user's mind-set. The need for query expansion comes from the fact that it is difficult to formulate a well-designed query that gives relevant results as per user's expectations. In this paper, query expansion is performed by adding new terms that users generally skip in their query assuming them to be common sense. This common sense is the link between the terms of the original query. We used ConceptNet, also called Common Sense Network, to add the missing terms. Experimental results show that the proposed method of query expansion greatly enhance the efficiency obtained over traditional queries.